2005
DOI: 10.1080/17446540500143848
|View full text |Cite
|
Sign up to set email alerts
|

Forecast performance of neural networks and business cycle asymmetries

Abstract: Forecast performance of artificial neural network models are investigated using Ashley et al. (1980) and the neural network nonlinearity test proposed by Lee et al. (1993) is employed to find possible existence of business cycle asymmetries in Canada, France, Japan, UK and USA real GDP growth rates. The results show that neural network models are more accurate than linear models for in-sample forecasts. However, when comparing the out-of-sample, linear models performed better than neural network models in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The procedure for the AGS test is also described in Bradshaw and Orden (1990) and Kiani et al (2005). Figures 1-8 confirm the results described above.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The procedure for the AGS test is also described in Bradshaw and Orden (1990) and Kiani et al (2005). Figures 1-8 confirm the results described above.…”
supporting
confidence: 75%
“…Qi and Wu (2003), who employ an ANN model with monetary fundamentals, find that their model cannot supass the random walk model. Alternatively, Kiani (2005) and Kiani et al (2005) use ANN models with macroeconomic time series and find that these outperform the linear as well as other nonlinear models employed. O' Connor and Madden (2005) evaluate the effectiveness of using ANNs with external indicators, such as commodity prices and currency exchange rates, in predicting movements in the Dow Jones Industrial Average index.…”
Section: Introductionmentioning
confidence: 99%
“…10. The procedure for the AGS test is also described in Bessler and Brandt (1992), Bradshaw and Orden (1990), Kastens and Brester (1996), and Kiani et al (2005).…”
Section: Ags Testmentioning
confidence: 99%
“…Qi and Wu (2003), who employ an ANN model with monetary fundamentals, find that their model cannot beat the random walk model. Alternatively, Kiani (2005) and Kiani et al (2005) used ANN models with macroeconomic time series and found that they outperformed the linear as well as other nonlinear models they employed. Lisi and Schiavo (1999) perform a detailed comparison of neural network and chaotic models for predicting monthly exchange rates.…”
Section: Introductionmentioning
confidence: 96%
“…Qi and Wu () show that their model cannot beat the random walk model by implementing a shallow neural networks approach with monetary indicators. In contrast, Kiani and co‐workers (Kiani, ; Kiani, Bidarkota, & Kastens, ) employed shallow neural networks with macroeconomic time series and proved that shallow neural networks perform better than the linear model.…”
Section: Literature Reviewmentioning
confidence: 99%